Genome‐wide association study of grain iron and zinc concentration in common bean (Phaseolus vulgaris) - Gelaw, Yonas Moges; Eleblu, John S. Y.; Ofori, Kwadwo; Fenta, Berhanu Amsalu; Mukankusi, Clare; Offei, Samuel Kwame (Wiley, 2023)
Common bean is one of the widely consumed food security crop in Africa, Asia and South America. It is a rich source of protein, minerals and micronutrients. High genotype by environment interaction is one of the main challenge in breeding for high grain micronutrient concentration. The objective of this study was to estimate SNP markers associated with grain Fe and Zn concentration using 289 common bean genotypes and 11,480 SNP markers. The study revealed that 43 quantitative trait loci (QTLs) were associated with grain Fe and Zn concentration. Five quantitative trait nucleotides (QTNs), that is, QTN Fe_1.1, QTN Fe_6.3, QTN Fe_6.5, QTN Fe_10.3 and QTN Fe_11.6 were detected both at Haramaya and Melkassa locations. Two of the markers, that is, QTN Fe_6.3 and QTN Fe_6.5, were located on chromosome 06 while QTN Fe_1.1, QTN Fe_10.3 and QTN Fe_ 11.6 were residing on chromosomes 01, 10 and 11, respectively. Among these, QTN Fe_11.6 had a large and positive consistent effect across locations. The five stable QTNs along with the potential candidate genes could be used for Fe biofortification through marker assisted selection.